2015
DOI: 10.1021/jacs.5b05629
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol to Fabricate Nanostructured New Phase: B31-Type MnS Synthesized under High Pressure

Abstract: Synthesis of nanomaterials with target crystal structures, especially those new structures that cannot be crystallized in their bulk counterparts, is of considerable interest owing to their strongly structure-dependent properties. Here, we have successfully synthesized and identified new-phase nanocrystals (NCs) associated with orthorhombic MnP-type (B31) MnS by utilizing an effective high-pressure technique. It is particularly worth noting that the generated new structured MnS NCs were captured as expected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 49 publications
(69 reference statements)
16
80
0
Order By: Relevance
“…15,16 High pressure is another significant factor that can influence structural properties in extreme cases. [17][18][19] However, the effects of strain or pressure on OMHPs are just 4 beginning to be explored. With the use of diamond anvil cells (DAC), the pressure-induced striking piezochromism and electronic conductivity of 2D Cu-Cl perovskites have been reported recently.…”
mentioning
confidence: 99%
“…15,16 High pressure is another significant factor that can influence structural properties in extreme cases. [17][18][19] However, the effects of strain or pressure on OMHPs are just 4 beginning to be explored. With the use of diamond anvil cells (DAC), the pressure-induced striking piezochromism and electronic conductivity of 2D Cu-Cl perovskites have been reported recently.…”
mentioning
confidence: 99%
“…Application of pressure up to 22.84 GPa caused anoticeable color change in the luminescence of Y-CDs and the observed color was shifted from yellow (557 nm) to bluegreen (491 nm), as shown in Figures 3b,c. [16] We carried out further experiments on the PL spectra by repeatedly exerting and releasing pressure on the Y-CDs. [15] Nevertheless,a st he applied pressure decreased from 22.84 to 0GPa, it was found that the PL spectra of Y-CDs were nearly identical, which is markedly different from the traditional piezochromic behavior (Figure 3d).…”
mentioning
confidence: 99%
“…[6] These complex but interesting transitions provide ar are opportunity to study the fundamentals of chemical bonding and to understand the structural behaviors of the minerals inside Earths crust and mantle. [8,9] It is established that the structural stability of ac ompound subjected to high pressure depends not only on the crystal structure but also,t osome extent, on the metal-ligand bonding strength especially when magnetolattice coupling is involved in the phase transition. [8,9] It is established that the structural stability of ac ompound subjected to high pressure depends not only on the crystal structure but also,t osome extent, on the metal-ligand bonding strength especially when magnetolattice coupling is involved in the phase transition.…”
mentioning
confidence: 99%
“…[8,9] It is established that the structural stability of ac ompound subjected to high pressure depends not only on the crystal structure but also,t osome extent, on the metal-ligand bonding strength especially when magnetolattice coupling is involved in the phase transition. [8,9] Herein, we present our results on the structural and Mn 2+ spin-state behavior of MnS and MnSe under compression obtained by means of combined in situ synchrotron X-ray diffraction and X-ray emission spectroscopy.T he first aim is to verify if the pressure-driven lattice collapse is universal in manganese chalcogenides.T he other aim is to gain more insight into the interplay between lattice,orbital, and magnetism during such an abnormal phase transition. Thus,aninteresting question arises as to whether heavy manganese chalcogenides also experience al arge pressure-induced lattice collapse.O n the other hand, both experimental and theoretical results on MnS and MnS 2 suggested that the spin-state transition of Mn 2+ might play as ignificant role in the lattice collapse process but without any direct evidence.…”
mentioning
confidence: 99%